2013
DOI: 10.3233/bme-130754
|View full text |Cite
|
Sign up to set email alerts
|

Reversing charges or how to improve Wharton's jelly mesenchymal stem cells culture on polyelectrolyte multilayer films

Abstract: BACKGROUND: Polyelectrolyte multilayer (PEMs) films made of poly(allylamine hydrochloride) (PAH) as polycation and poly(styrene sulfonate) (PSS) as polyanion, with a PAH ending layer, can be used as a coating in order to improve the antithrombogenicity and patency of vascular grafts in vascular engineering field. They induce strong adhesion of mature endothelial cells on glass, expanded polytetrafluoroethylene and cryopreserved arteries. Despite their outstanding effect on mature and progenitor endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…All procedures were done in accordance with the authorization and registration number DC-2014-2262 given by the French National "Cellule de Bioéthique". Stem cells, enzymatically isolated from fresh human umbilical cords obtained after full-term births [24], were cultured in complete culture medium [alpha-Minimal Eagle Medium (α-MEM, Lonza) supplemented with 10% decomplemented fetal bovine serum (FBS), 1% Penicillin/Streptomycin/Amphotericin B and 1% Glutamax® (v/v, Gibco)] and used in our experimental procedure at the 4th passage (P4).…”
Section: Biological Testsmentioning
confidence: 99%
“…All procedures were done in accordance with the authorization and registration number DC-2014-2262 given by the French National "Cellule de Bioéthique". Stem cells, enzymatically isolated from fresh human umbilical cords obtained after full-term births [24], were cultured in complete culture medium [alpha-Minimal Eagle Medium (α-MEM, Lonza) supplemented with 10% decomplemented fetal bovine serum (FBS), 1% Penicillin/Streptomycin/Amphotericin B and 1% Glutamax® (v/v, Gibco)] and used in our experimental procedure at the 4th passage (P4).…”
Section: Biological Testsmentioning
confidence: 99%
“…WJ-MSCs cultivated on PAH ending coating resulted in a disturbance of cell monolayer, whereas on PSS ending coating, WJ-MSCs exhibited a normal cell growth, suitable for endothelial cell differentiation. 33 PAH/PSS is a very-well-characterized multilayer system that has already been studied for biomedical applications.32 Figure 1(a) represents the evolution of the thickness of PAH/ PSS, measured by OWLS, for different number of bilayers. The alternated deposition of PAH and PSS allowed to increase the thickness of the film up to 15 nm for four bilayers.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, eight alternate PAH and PSS layers were deposited and (PAH-PSS) 4 films (PEMs) were then built up according to Ref. 33. Cleaned glass substrates coated with type-I collagen (COL-I, 100 lg/mL, BD-Bioscience) were used as control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Previsous studies in our lab have also demonstrated that poly(allylamine hydrochloride) (PAH) and poly(styrene sulfonate) (PSS) polyelectrolyte multilayer films improve culturing of WJ-MSCs and ECs. 22,23 We therefore used these two stimuli alone and in combination, to induce endothelial differentiation of WJ-MSCs. The obtained data showed that the differentiation into an endothelial phenotype was induced by cultivating WJ-MSCs at the fourth passage, seeded on (PAH/PSS) 4 film-coated glass slides, in the presence of EGM-2.…”
Section: Wj-mscs Acquire Endothelial Phenotype and Function On Differmentioning
confidence: 99%